KAJIAN IKONOGRAFI KARYA DULLAH â€œPRAKTIK TENTARA PENDUDUKAN ASINGâ€ - Adisukma, Wisnu (Acintya, 2016)
The article with the title Iconography Study of Work Dullah “Army Practice of Foreign Occupation“ intended to seek the textual and contextual meaning of painters Dullah. With the approach of iconography will be obtained meaning that deeper and broader than a work of art. Through this approach, the artwork will be a major concern in reviewing the history of art, nevertheless alsonecessary to understand the contextual and symbolic aspects. At the time of independence, Dullah many immortalize the events related to the struggle of Indonesian nation in seizing and maintaining independence in his works. Dullah even led a group of young artists to paint directly events duringthe occupation of Yogyakarta as an effort documenting the history of the national struggle. One of his very powerful is the “Army Practice of Foreign Occupation“ that depicts cruelty colonizers against the indigenous population. In this case the work Dullah Practice Foreign Occupation Army will findits context as understood by tracing the history of socio-cultural-years 1940-1950an. From the work we can find out how the socio-historical situation of the community when the colonial era.Keywords: Dullah, Iconography, Army Practice of Foreign Occupation.